VIRTUAL REALITY HYPNOSIS FOR PAIN ASSOCIATED WITH RECOVERY FROM PHYSICAL TRAUMA, - Patterson, David R. (2010)
Pain following traumatic injuries is common, can impair injury recovery and is often inadequately treated. In particular, the role of adjunctive nonpharmacologic analgesic techniques is unclear. The authors report a randomized, controlled study of 21 hospitalized trauma patients to assess the analgesic efficacy of virtual reality hypnosis (VRH)—hypnotic induction and analgesic suggestion delivered by customized virtual reality (VR) hardware/software. Subjective pain ratings were obtained immediately and 8 hours after VRH (used as an adjunct to standard analgesic care) and compared to both adjunctive VR without hypnosis and standard care alone. VRH patients reported less pain intensity and less pain unpleasantness compared to control groups. These preliminary findings suggest that VRH analgesia is a novel technology worthy of further study, both to improve pain management and to increase availability of hypnotic analgesia to populations without access to therapist-provided hypnosis and suggestion.